Workplace Burnout Among Employees in Academic Institutions - Beverly, Fernandez; April, Santos (Asian Journal of Multidisciplinary Studies, 2024)
This study investigates workplace burnout among employees of Pangasinan State University, emphasizing its prevalence, demographic correlations, and dimensions such as physical, emotional, psychological, social, spiritual, financial, and work environment factors. The aim is to provide a comprehensive understanding of burnout dynamics and recommend targeted interventions to enhance employee well-being and institutional effectiveness. Utilizing a descriptive correlational research design. The study focuses on a diverse sample of teaching and non-teaching staff, employing the Workplace Burnout Questionnaire with specific measures on various dimensions, including Physical, Emotional, Psychological, Social, Spiritual, Financial, and Work Environment Scales. Data were collected through a Google Form, and Spearman's rho, a non-parametric test, was used for analysis due to unequal sample distribution. Findings reveal a moderate positive correlation between age and the General Scale, suggesting that older employees experience higher levels of overall workplace burnout. However, no significant correlations were observed between age and specific scales, emphasizing the nuanced relationship between age and distinct burnout dimensions. A weak negative correlation emerged between age and the Psychological Scale, indicating that younger employees may face higher psychological burnout. In terms of demographic variables, civil status demonstrated positive associations with the General and Financial Scales, suggesting higher civil status correlates with increased overall burnout and decreased financial burnout. Educational attainment and employment status exhibited positive correlations with the Social Scale, indicating higher education and specific employment statuses are linked to increased social burnout. These findings underscore the need for targeted interventions considering demographic variations. The study recommends implementing evidence-based programs, fostering work-life balance, and establishing psychological support services. Future research should delve into qualitative aspects, explore intricate relationships between demographics and burnout, and conduct longitudinal studies to assess the effectiveness of interventions over time. This research contributes to a comprehensive understanding of workplace burnout and informs strategies to enhance employee well-being within the university context.